Integrated livestock innovation enables substantial changes in Nepal’s dairy animal productivity - Varijakshapanicker, Padmakumar; Bhatt, Prem R.; Khanal, Supreksha; Teufel, Nils (International Livestock Research Institute, 2024)
In Nepal, livestock is considered to have significant potential to contribute to alleviating rural poverty, ensure food security at the household and national levels, as well as aid in achieving import substitution to conserve foreign exchange. The productivity of the livestock sector is, however, far too low, even when compared to other Asian countries. International Farm Comparison Network (IFCN) data shows that China and Thailand have the highest yield of 3-5 tons per cow per year whereas it is lower than 1 ton per cow per year in Nepal. The production of native buffalo breeds is only about 900 liters/lactation compared to the Murrah which are crossbred yielding 1500 liters/lactation, which is still far behind the genetic potential of 2300 liters.